Environmental Impact Assessment of the Petroleum Industries: A Review - Abdulhassan, Zainab Y.; Alhares, Hasanain S. (PROSPECTIVE RESEARCHES, 2025)
This research aims to shed light on the phenomenon of environmental pollution and its effects on the environment in general, and oil pollution in particular. In recent years, pollution has taken many forms, significantly impacting the composition of natural elements, such as air, soil, and water pollution. The impact of pollution then extends to all areas of human life. The research reviewed the environmental and economic effects of oil pollution. The gasses released during the evaporation or breakdown of spilled oil particles make oil and its derivatives extremely hazardous. In addition to crude oil, other harmful gasses including hydrogen sulfide (H2S) are also present in oil. Oil poses a significant threat to marine life, as it can poison or kill marine organisms. The effects of an oil spill range from immediate to long-term. Immediate damage is felt in marine animals and plants that live on the water surface, such as birds and seals, while long-term damage occurs as a result of the oil's decomposition and its negative impact on the marine food chain. In addition, spilled oil poses a risk to industrial facilities and oil refineries, due to the potential for fires or explosions, increasing the economic and environmental damage associated with these incidents. The greatest impact is on desalination plants, as toxic hydrocarbons can contaminate drinking water, causing these plants to shut down for potentially extended periods. Oil spills have significant economic impacts, including production shutdowns, impacts on fish stocks, and the high costs of combating and cleaning up affected beaches. The invasive emissions from the oil factories contribute to the occurrence of acid rain. Acid rain is the third most significant environmental problem in the world after global warming and ozone depletion. It is the most significant problem resulting from local air pollution, which is carried by winds across the borders of neighboring countries and causes serious damage to terrestrial and aquatic ecosystems and human health.